2020
DOI: 10.4067/s0717-95022020000300726
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis of Morphometric Evaluation from the Heart Valves for Age Estimation in Thai Population

Abstract: GUMPANGSETH, T.; KOMUTRATTANANONT, P.; PALEE, P.; PRASITWATTANASEREE, S. & MAHAKKANUKRAUH, P. Image analysis of morphometric evaluation from the heart valves for age estimation in Thai population. Int. J. Morphol., 38(3):726-730, 2020. SUMMARY:Determination of age represents one of the most important aspects in forensic identification. Through aging, changes can occur in morphological structures of the heart valves. The objective is to examine the relationship between the dimensions of the rigth atrioventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 13 publications
2
4
4
Order By: Relevance
“…Contrast to our studies Gumpangseth et al. (2020) reported in humans that, the septal leaflet was the largest followed by posterior and anterior leaflets of tricuspid valve. Rohilla et al.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrast to our studies Gumpangseth et al. (2020) reported in humans that, the septal leaflet was the largest followed by posterior and anterior leaflets of tricuspid valve. Rohilla et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrast to our findings, Gumpangseth et al. (2020) reported that the length and height of three cusps were similar.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations